Konstrukcje hybrydalne z Panje- w języku niemieckim - Kułacz, Sławomir (Papers in Linguistics, 2019)
The article discusses the origins and the spread of hybrid words containing the element Panje- borrowed from Polish into German. The first documented uses of the hybrid Panjewagen date back to the early months of World War One when the German Army entered the Kingdom of Poland (also known as Russian Poland). Later, when German troops advanced further East, more hybrids of this kind appeared in the soldiers’ slang. Twenty years on, the Wehrmacht relied heavily on requisitioned wagons and workhorses and it is when the words Panjewagen and Panjepferd were revived and gained even more popularity. It should be of no surprise, then, that they can be found in many unabridged dictionaries of German and even in the titles of a number of books.